A full-scale field experiment to evaluate the cooling performance of a novel composite embankment in permafrost regions. (April 2016) - Zhang, Mingyi; Lai, Yuanming; Wu, Qingbai; Yu, Qihao; Zhao, Tao; Pei, Wansheng; Zhang, Jianming
Highlights: High-grade highways may destabilize underlying permafrost in permafrost regions. The cooling effect of a novel composite embankment is evaluated by a field experiment. The composite embankment can effectively protect the underlying permafrost in the field experiment. This composite embankment is a better candidate for separated high-grade highways in permafrost regions. Abstract: High-grade highways designed for large traffic volumes need wider embankments than railways and low-grade highways. In permafrost regions, a wide and dark-colored asphalt pavement surface of high-grade highways may destabilize underlying permafrost if the embankment is insufficiently cooled, especially under a warming climate. However, the embankments with single commonly cooling technique, e.g. two-phase closed thermosyphon (TPCT) embankment and crushed-rock embankment cannot satisfy the cooling requirement of high-grade highways because of their limited cooling capacities. Here, we use a full-scale field experiment of a separated high-grade highway with double lanes each direction at Beiluhe in the Qinghai-Tibet Plateau to investigate the thermal characteristics of a novel composite embankment combined with L-shaped TPCTs, crushed-rock revetments and insulation, as well as an unprotected embankment (as a control). Experimental results indicate that the composite embankment can effectively cool the underlying permafrost and raise the permafrost table under the separated high-grade highway with a wide and dark-colored pavement, whereas the unprotected embankment cannot. This composite embankment should be considered for application to separated high-grade highways with double lanes each direction in permafrost regions, such as the planned Qinghai-Tibet Expressway.